Full of grace - Frank, Dorothea Benton (New York : Ballantine Books, 2006)
"The rich atmosphere of South Carolina, both Hilton Head and Charleston, is brought vividly to life by Dorothea Benton Frank, a South Carolina native who, with her evocative prose, makes you smell the sea air, see the palmettos, and savor the sweet tea, but this time it will come with a side of antipasti. Hilton Head, South Carolina is retirement heaven -- at least it's supposed to be, but for Big Al and Connie, the move from New Jersey to this southern paradise has been fraught with just a few complications. Especially for their daughter, Grace" --from the publisher.
Keywords: Italian American women -- Fiction; Italian American women -- Fiction; Charleston (S.C.) -- Fiction; Charleston (S.C.) -- Fiction; Hilton Head (S.C.) -- Fiction; Hilton Head (S.C.) -- Fiction; Domestic fiction